Observations on the Concept of “History” (19th–20th centuries)(Questions of Theory of History) - Hakobyan, Ararat; Hakobyan, Vahagn (History and Culture, 2026)
Examining the observations of representatives of European, and partly Russian, historical and philosophical thought on the meaning, understanding, and significance of the concept of "history", we can come to the following conclusions. First and foremost, history is an integral part of humanity’s conscious life. Without history, there is no human or human society. History is the memory of humanity. Without memory, there is no history. History is a repository of material and spiritual wealth created by human society, from which we learn, gain experience, and draw lessons for the present and future. The meaning of history should be seen not in the class division and hostility of people towards each other, but in ensuring the freedom and progress of people and nations. As long as the world and humanity exist, history will exist. The educational and instructive role of history is undeniable, both in the achievements and successes left to humanity, and in humanity’s aspirations for freedom and development reflected on its pages, as well as in the inevitably accompanying sad pages and sometimes failures. The experience of history shows that new challenges await humanity in the future. This is evidenced and confirmed by European historical and philosophical thought, as well as, to some extent, by modern real life and reality. The entire system of values created by humanity accumulates in history. One of the main merits of history is that it contributes to the development of people’s intellectual abilities, science in general, and spiritual and cultural progress and development. History is a means of self-knowledge of the human spirit. In addition, history is called upon to understand the present through knowledge of the past and to correctly orient oneself in the future. Due to the cause-and-effect relationship between the past and the present, spiritual and cultural inheritance occurs as information transmitted to generations. Knowledge of history also contributes to strengthening the patriotic aspirations of each nation, enriching socio-political knowledge, and developing scientific and spiritual thought and values in general. History is especially valuable and important for Armenia and Armenian society, especially when we consider its rich, suffering, instructive, and edifying path of millennia, directed towards the present and future. Armenian history, like that of many peoples, in addition to socio-economic and political aspects, has also borne the imprint of the ontological over the centuries. And this, apparently, was due, on the one hand, to the geopolitical position and conditions of Great Armenia, and on the other hand, to the peculiarities of the national mentality. But with all this, Armenia and the Armenian people undoubtedly constitute an integral and inalienable part of world history.